Answer:
The average rate of change of the function over the interval is 5.
Step-by-step explanation:
Average rate of change of a function:
The average rate of change of a function f(x) over an interval [a,b] is given by:
[tex]A = \frac{f(b)-f(a)}{b-a}[/tex]
Interval -3 less-than-or-equal-to x less-than-or-equal-to 3
This means that [tex]a = -3, b = 3[/tex]
[tex]f(x) = x^2 + 3x + 6[/tex]
So
[tex]f(b) = f(3) = (3)^2 + 3(3) + 6 = 9 + 9 + 6 = 24[/tex]
[tex]f(a) = f(-3) = (-3)^2 + 3(-3) + 6 = 9 - 9 + 6 = 6[/tex]
Average rate of change
[tex]A = \frac{f(b)-f(a)}{b-a} = \frac{24+6}{3-(-3)} = \frac{30}{6} = 5[/tex]
The average rate of change of the function over the interval is 5.